Manganese levels in infant formula and young child nutritional beverages in the United States and France: Comparison to breast milk and regulations - Frisbie, Seth H. (PLoS One, 2019)
Exposure to high levels of manganese (Mn) in children has recently been associated with adverse neurodevelopmental effects. Current infant formula regulations for Mn content were set between 1981 (United States), 2006 (European Union, France), and 2007 (Codex Alimentarius) prior to the publication of much of the growing body of research on the developmental neurotoxicity of Mn. In this study, we sought to measure the concentrations of Mn in some infant formulas and young child nutritional beverages available on the United States (US) and French markets using ion beam analysis by particle induced X-ray emission (PIXE) spectrometry and then compare the analytical results to concentrations reported in the literature for breast milk and applicable infant formula regulations and guidelines. We were particularly interested in measuring Mn concentrations in product types for which there is very little data from previous surveys, especially soy-based, rice-based, goat-milk based, chocolate-flavored, and nutritional beverages for young children that are not regulated as infant or follow-on formulas (e.g. “toddler formulas” and “toddler powders”). We purchased 44 infant formulas and young child nutritional beverage products in the US and France with varying protein sources (cow-milk, goat-milk, soy, rice) labelled for birth to 3 years. We selected these samples using maximum variation sampling to explore market extremes to facilitate comparisons to regulatory limits. Since this sampling method is non-probabilistic, other inferences cannot be made beyond this set of samples to the overall markets. We used ion beam analysis to measure the concentrations of Mn in each product. The range of measured Mn concentrations in the products is 160–2,800 μg/L, substantially higher than the 3–6 μg/L mean Mn concentration reported in human breast milk. All products satisfied national and Codex Alimentarius Commission (CAC) international standards for minimum Mn content in infant formulas; however, 7/25 of the products purchased in the US exceeded the CAC Guidance Upper Level of 100 μg Mn/kcal for infant formula.